Ileal lymphangioma Mimicking Small Bowel Cancer - Nishat N. Siddique; Wei M. Ong; Suat C. Ng (World Journal of Colorectal Surgery)
Small bowel lymphangiomas (SBLs) are a rare clinical entity in adults and can be challenging to diagnose preoperatively due to their nonspecific imaging findings. We present a case of a 71-year-old man with previously resected T1N0 sigmoid adenocarcinoma presented with a 25-mm polypoid small bowel lesion on surveillance CT. A push enteroscopy was unremarkable; however, diagnostic laparoscopy and small bowel resection revealed a polypoid mass in the mid-ileum excreting milky fluid. Histopathology was consistent with a lymphangioma. SBLs have a diverse range of clinical presentations, although most are asymptomatic. Push enteroscopy is the preferred investigative modality, as it allows biopsy; however, it may fail to reach the lesion depending on its location. Macroscopically, lymphangiomas appear as smooth, polypoid masses with white mucosal spots and exude milky chylous fluid when compressed. Resection is the primary treatment for symptomatic lesions. For asymptomatic cases, patients should be counselled on the risks and benefits of intervention versus surveillance.